Validation of the RUDAS for the Identification of Dementia in Illiterate and Low-Educated Older Adults in Lima, Peru - Custodio, Nilton; Montesinos, Rosa; Lira, David; Herrera-Perez, Eder; Chavez, Kristhy; Reynoso-Guzman, Willyams; Pintado-Caipa, Maritza; Cuenca, José; Gamboa, Carlos; Metcalf, Tatiana (Frontiers in Neurology, 2020)
Objectives: To evaluate the performance of the Peruvian version of the Rowland Universal Dementia Assessment Scale (RUDAS-PE) in discriminating between controls and patients with mild cognitive impairment (MCI) and dementia in an illiterate population with low-levels of education. Methods: We compared the cognitive performance of 187 elderly subjects who were illiterate (controls n=60; MCI n=64; dementia n=63). Neuropsychological measures included the RUDAS-PE, Mini-Mental State Examination (MMSE), INECO Frontal Screening (IFS), and Pfeffer Functional Activities Questionnaire (PFAQ). The results were compared to a neuropsychological evaluation (gold standard), including use of Clinical Dementia Rating (CDR) scores. Results: We found a Cronbach’s alpha was 0.65; Spearman’s correlation coefficient was 0.79 (p < 0.01). The area under the receiver operating characteristics curve for the RUDAS to discriminate dementia from MCI was 98.0% with an optimal cut-off <19; whereas, to differentiate MCI and controls was 98.0% whit an optimal cut-off <23. Conclusions: Based on its excellent psychometric properties, we find the RUDAS-PE suitable to aid in the opportune detection of dementia in a geriatric illiterate population with low-levels of education.